Solid state bioconversion of seaweed for production of protein enriched fish feedstock - Jamal, Parveen; Saheed, Olorunnisola Kola; Jaswir, Irwandi; Tijani, Ruqayyah I. D. (2014)
Sustainable and economical source of fish feed ingredients is a cornerstone to successful and profitable fish production for small farm holder and industrial applications. Solid State Bioconversion (SSB) was conducted to optimize process parameters necessary for optimum protein synthesis using seaweed as carbon source. Phanerochaete chrysosporium (P. chrysosporium) was cultivated under SSB on sea weed for 7days. Single factor optimization revealed optimum protein synthesis at 70% moisture content, 9% inoculum size and 7% of minerals. Protein synthesis increased to 120.29 mg/g after optimization by response surface; all parameters showed positive interactions in increasing protein synthesis and the model was significant at p˂0.05. Validation of the model saw protein production falling within 10% tolerable points to produce 109.54 mg/g of protein.